2002
DOI: 10.1111/j.1745-4530.2002.tb00565.x
|View full text |Cite
|
Sign up to set email alerts
|

Residual Gas Volume Effect on Quality of Retort Pouch Wet‐pack Pears

Abstract: Wet pack pears in retort pouches were studied for six months. Four selected residual gas volumes [10, 15, 20 and 30 cubic centimeters (cc)] were used to determine the influence of residual gas volume on physicochemical and sensory attributes. Three storage temperatures (4.4, 26.7 and 37.8C) were used to carry out an accelerated shelf‐life study. Residual gas of 30 cc promoted faster darkening and higher ascorbic acid degradation than the rest of the volumes studied (α≤ 0.01). No significant effect of residual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Some reports have shown that pH may decrease during nonenzymatic browning due to the appearance of carbonyl compounds (Roig et al, 1999). However, it has also been reported that pH increases during the storage of retort pouch wetpack pears (Olivas et al, 2002). No changes in °Brix were observed in cashew apple (pH 4.4) during storage; the constant concentration of soluble solids, reducing and total sugars suggested that there was no participation of sugars in the nonenzymatic browning reactions (Damasceno et al, 2008).…”
Section: Ph and °Brix During Storagementioning
confidence: 98%
“…Some reports have shown that pH may decrease during nonenzymatic browning due to the appearance of carbonyl compounds (Roig et al, 1999). However, it has also been reported that pH increases during the storage of retort pouch wetpack pears (Olivas et al, 2002). No changes in °Brix were observed in cashew apple (pH 4.4) during storage; the constant concentration of soluble solids, reducing and total sugars suggested that there was no participation of sugars in the nonenzymatic browning reactions (Damasceno et al, 2008).…”
Section: Ph and °Brix During Storagementioning
confidence: 98%
“…Its presence has been shown to affect physico-chemical, sensory properties and product shelf life (Olives, 2002). The residual air in the pack should be less than 2% of the volume of the pouch contents (Venugopal, 2006) and higher levels of air in the pouch may result in deflating of the pouches during thermal processing.…”
Section: Heat Sterilization Process In Retort Pouchesmentioning
confidence: 99%
“…Residual air has been studied as a critical factor in relation to product quality and shelf life after processing (Olivas and others ; Rodríguez and others ; Sepülveda and others ). It has been established that when there are large levels of residual air relative to the total pouch volume, the gas acts as an insulator increasing process times and decreasing the average heating slope (Rodríguez and others ; Campbell and Ramaswamy ).…”
Section: Introductionmentioning
confidence: 99%